Effect of Benzo[a]pyrene-DNA Adduct in Cord Blood on the Neurodevelopment of 12-Month-Old Infants in Qingdao City - Zhang Y (Dove Medical Press, 2019)
Yong Zhang,1,* Yuehua Yang,2,* Qian Zhang,3,* Jing Cui,4 Abdul Rahaman,5 Xiao-Rong Huang,6,7 Ya Su,4 Ruqin Gao,4 Bingling Wang,4 Zulqarnain Baloch6 1Department of Paediatric Surgery, Qingdao Women and Children’s Hospital, Qingdao, People’s Republic of China; 2Department of Obstetrics, The Affiliated Central Hospital of Qingdao University, Qingdao, People’s Republic of China; 3Department of Child Health Care, Huangdao Maternity and Child Health Care Hospital of Qingdao, Qingdao, People’s Republic of China; 4Department of Environmental Health, Qingdao Centers for Disease Control and Prevention/Qingdao Institute for Preventive Medicine, Qingdao, People’s Republic of China; 5School of Food Science and Engineering, South China University of Technology, Guangzhou 510640, People’s Republic of China; 6Biomedical Research Center, Northwest Minzu University, Lanzhou 730030, People’s Republic of China; 7College of Veterinary Medicine, South China Agricultural University, Guangzhou, 51062, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zulqarnain BalochBiomedical Research Center, Northwest Minzu University, Lanzhou 730030, People’s Republic of ChinaTel/Fax +8618344564625Email znbalooch@yahoo.comBingling WangDepartment of Environmental Health, Qingdao Institute for Preventive Medicine, No. 175 Shandong Road, Qingdao 266033, People’s Republic of ChinaTel +86 532 85621975Fax +86 532 85623909Email binglingw@yeah.netIntroduction: The study was designed to explore the possible adverse effects of prenatal polycyclic aromatic hydrocarbons (PAHs) on the neurodevelopment of the infants at the age of 12 months in a birth cohort in Qingdao of China. Benzo[a]pyrene (BaP)-DNA adduct level in umbilical cord blood was measured by enzyme immunoassay.Methods: Child neurodevelopment was assessed at both 6 months and 12 months of age using the Gesell Development Inventory (GDI).Results: This study results reveal that multivariate linear analysis, cord BaP-DNA adduct level was inversely associated with developmental quotient score in the adaptive domain [β = −0.08; 95% CI: (−0.16, −0.003); p = 0.04], gross motor domain [β = −0.10; 95% CI: (−0.20, −0.01); p = 0.02], fine motor domain [β = −0.15; 95% CI: (−0.25, −0.05); p = 0.01], language domain [β = −0.12; 95% CI: (−0.21, −0.03); p = 0.02], and personal–social domain [β = −0.13; 95% CI: (−0.22, −0.04); p<0.01]. Further, multivariate logistic regression analysis showed increased cord BaP-DNA adduct levels associated with increased odds of delayed in language domain.Conclusion: In conclusion, the study suggested that prenatal PAH exposure monitored by umbilical cord blood BaP-DNA adducts may adversely affect the neurodevelopment of the infants at 12 months of age.Keywords: neurodevelopment, PAH-DNA adducts, infant, polycyclic aromatic hydrocarbons, China